Medicina ancestral de las mujeres diaguita en el norte chico chileno - Rodríguez Venegas, Viviana (2024)
Qualitative research that investigates the knowledge and cultural practices of the diaguita women of the Chilean northern Chico and their relationship with ancestral medicine. The diaguita have been made invisible as protagonists of the healing processes, in an andro-centered and subalternizing treatment, which contrasts with the abundant evidence on the importance of women in the survival of ancestral medicine. The methodology was based on a feminist ethnography carried out in the regions of Atacama and Coquimbo (Chile), between 2021 and 2023, with traditional diaguita authorities. The results show the characteristics, elements and strategies used in the healing processes developed by diaguita women, also highlighting the importance of medicinal plants. It is concluded that the diaguita are carriers and transmitters of ancestral knowledge and traditional practices in a matrilineal and intergenerational manner, establishing ancestral medicine as a form of decolonizing cultural resistance.